1998
DOI: 10.1086/515264
|View full text |Cite
|
Sign up to set email alerts
|

Mother‐to‐Infant Transmission of GB Virus C/Hepatitis G Virus: The Role of High‐Titered Maternal Viremia and Mode of Delivery

Abstract: To study mother-to-infant transmission of GB virus C/hepatitis G virus (GBV-C/HGV), blood samples of infants born to carrier mothers were collected beginning 3 months after birth and were tested for GBV-C/HGV RNA until 1 year of age. Of 2046 mothers, 2.1% were positive for GBV-C/ HGV RNA, and 25 of their infants were followed for a median of 12 months. Thirteen infants (52%) were viremic, and infection became persistent in all. Maternal GBV-C/HGV RNA levels of this group were ú10 7 copies/mL. Nucleotide sequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
35
5

Year Published

2000
2000
2003
2003

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 21 publications
5
35
5
Order By: Relevance
“…A group of 25 GBV-C/HGV-infected mothers who had participated in our previous study [Lin et al, 1998] served as a second study group. Serum samples from both groups were collected during prenatal examinations and an assay for hepatitis B surface antigen (HBsAg) and then an assay for hepatitis B e antigen (HBeAg) were performed if specimens were positive for HBsAg.…”
Section: Subjectsmentioning
confidence: 99%
See 2 more Smart Citations
“…A group of 25 GBV-C/HGV-infected mothers who had participated in our previous study [Lin et al, 1998] served as a second study group. Serum samples from both groups were collected during prenatal examinations and an assay for hepatitis B surface antigen (HBsAg) and then an assay for hepatitis B e antigen (HBeAg) were performed if specimens were positive for HBsAg.…”
Section: Subjectsmentioning
confidence: 99%
“…Mothers were de®ned as carriers of TTV when serum specimens were positive for viral DNA at least twice within an interval of 3 months. Blood samples were collected from infants born to carrier mothers and were tested for TTV DNA and ALT starting from 3 months after birth until 1 year of age (usually every 2±3 months) [Lin et al, 1998]. …”
Section: Subjectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Anti-E2 antibody was found to be a neutralising antibody and it was shown that GBV-C infection was transitory in the majority of cases [Thomas et al, 1998;Lefrere et al, 1999]. GBV-C was originally found as a blood borne virus, but transmission by the sexual and vertical route has also been documented [Schmidt et al, 1996;Kao et al, 1997;Lin et al, 1998]. …”
Section: Introductionmentioning
confidence: 99%
“…Most GBV-C/HGV infections seem to be self-limiting and no clear-cut pathology has been ascribed to GBV-C/HGV. GBV-C/HGV is transmitted mainly by parenteral routes, such as contaminated blood products and intravenous drug abuse (IVDU) and also by vertical transmission [Fischler et al, 1997;Lin et al, 1998;Viazov et al, 1997a,b]. No definite explanation for the existence of both GBV-C/HGV RNA (1-3% [Linnen et al, 1996;Simons et al, 1995]) and antibodies (3-8%; [Dille et al, 1997]) in the general population has been provided.…”
Section: Introductionmentioning
confidence: 99%